Amphetamine- and nicotine-induced cross-sensitization in adolescent rats persists until adulthood - Santos, Gabriela C. [UNESP]; Marin, Marcelo Tadeu [UNESP]; Cruz, Fabio C. [UNESP]; DeLucia, Roberto; Planeta, Cleopatra da Silva [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Nicotine and psychostimulants are often abused in combination and drug abuse often begins during adolescence and can have long-term consequences. Behavioral sensitization has been suggested as an animal model of neuroplasticity implicated in the development of drug addiction. We evaluated whether the pretreatment with nicotine (0.4 mg/kg; s.c.) or amphetamine (5.0 mg/kg: i.p.) in adolescent rats [from postnatal day (P) 28 to P34] could induce cross-sensitization to nicotine and amphetamine when animals were challenged during both adolescence (P37) and adulthood (P70), in separate groups of animals. Adolescent animals pretreated with amphetamine displayed behavioral sensitization to nicotine. which persisted until adulthood. Moreover. adolescent animals pretreated with nicotine showed sensitized locomotor response to amphetamine in the adulthood. These data suggest that adolescents who abuse nicotine may be particularly susceptible to the effects of amphetamine and vice versa. Moreover. this increased vulnerability may persist through their development until adulthood.
Keywords: Adolescence; amphetamine; behavioral sensitization; drug addiction; locomotion; nicotine